2011
DOI: 10.1158/0008-5472.can-11-1262
|View full text |Cite
|
Sign up to set email alerts
|

ANGPTL4 Induction by Prostaglandin E2 under Hypoxic Conditions Promotes Colorectal Cancer Progression

Abstract: Prostaglandin E2 (PGE2), the most abundant COX-2–derived prostaglandin found in colorectal cancer, promotes tumor cell proliferation and survival via multiple signaling pathways. However, the role of PGE2 in tumor hypoxia is not well understood. Here, we show a synergistic effect of PGE2 and hypoxia on enhancing ANGPTL4 expression and that elevation of ANGPTL4 promotes colorectal cancer growth. PGE2 induces ANGPTL4 expression at both the mRNA and protein levels under hypoxic conditions. Moreover, hypoxia induc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
112
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(115 citation statements)
references
References 48 publications
(66 reference statements)
3
112
0
Order By: Relevance
“…Similarly, Huang and colleagues detected elevated cANGPTL4 from fine needle aspirates of breast tumors, basal cell carcinomas, melanomas, and in several cancer cell lines derived from breast, lung, and liver cancers (21). Consistent with the above findings, Kim and colleagues showed that colorectal cancer (CRC) cells only secrete cANGPTL4 proteins (25). A high ANGPTL4 expression in oral cancer correlates to an enhanced rate of tumorigenesis and a poor prognosis based on the tumor clinicopathology (Table 2; refs.…”
Section: Angptl4 Expression and Its Transcriptional Regulation In Hummentioning
confidence: 65%
See 2 more Smart Citations
“…Similarly, Huang and colleagues detected elevated cANGPTL4 from fine needle aspirates of breast tumors, basal cell carcinomas, melanomas, and in several cancer cell lines derived from breast, lung, and liver cancers (21). Consistent with the above findings, Kim and colleagues showed that colorectal cancer (CRC) cells only secrete cANGPTL4 proteins (25). A high ANGPTL4 expression in oral cancer correlates to an enhanced rate of tumorigenesis and a poor prognosis based on the tumor clinicopathology (Table 2; refs.…”
Section: Angptl4 Expression and Its Transcriptional Regulation In Hummentioning
confidence: 65%
“…Recently, PPARs have been implicated in the development of tumors (24). Studies have shown that ANGPTL4 is one of the PPAR target genes and contains several putative PPAR response element consensus sequences within its promoter (25). Reports have proposed that ANGPTL4 may be regulated by all 3 PPAR isoforms (PPARa, PPARb/d, and PPARg), suggesting that ANGPTL4 may exert tissuedependent effects governed by the differential expression of the PPAR isoforms (15).…”
Section: Angptl4 Expression and Its Transcriptional Regulation In Hummentioning
confidence: 99%
See 1 more Smart Citation
“…24,25 'PTGER1 (prostaglandin E receptor 1 (subtype EP1), 42 kDa)' is activated by COX-2/PGE-2 signaling that is overexpressed in 90% of sporadic colon carcinomas and is induced by hypoxia. 78,79 Another target that has shown to directly upregulate COX-2 expression is the 'HIST1H1A (histone cluster 1, H1a)', whose overexpression had been significantly associated with a shorter colorectal cancer-specific and overall survival. 80 Through a SRC-dependent pathway, PTGER1 activates the 'ANGPTL4 (angiopoietin-like 4)' protein that may promote colorectal carcinogenesis.…”
Section: Gene Expression Profiles and Deranged Signaling Pathwaysmentioning
confidence: 99%
“…80 Through a SRC-dependent pathway, PTGER1 activates the 'ANGPTL4 (angiopoietin-like 4)' protein that may promote colorectal carcinogenesis. 79 Upregulation of this pathway may drive FCCTX tumor development during anaerobic conditions, and this is supported by frequent findings of dirty necrosis during histological evaluations and downregulation of the aerobic oxidative phosphorylation metabolism genes such as 'ATP5L (ATP synthase, H þ transporting, mitochondrial Fo complex, subunit G),' 'ATP5A1 (ATP synthase, H þ transporting, mitochondrial F1 complex, a-subunit 1, cardiac muscle),' 'ATP5B (ATP synthase, H þ transporting, mitochondrial F1 complex, b-polypeptide),' and 'ATP5D (ATP synthase, H þ transporting, mitochondrial F1 complex, d-subunit)' (Figure 3). 25,37 Copy number gains and EGFR-mediated activation of SRC have been correlated to migration and invasion 81 ( Figure 3).…”
Section: Gene Expression Profiles and Deranged Signaling Pathwaysmentioning
confidence: 99%